Review on feature-based method performance in text steganography - Mohd Hilal Muhammad; Hanizan Shaker Hussain; Roshidi Din; Hafiza Samad; Sunariya Utama (Bulletin of Electrical Engineering and Informatics, 2021)
The implementation of steganography in text domain is one the crutial issue that can hide an essential message to avoid the intruder. It is caused every personal information mostly in medium of text, and the steganography itself is expectedly as the solution to protect the information that is able to hide the hidden message that is unrecognized by human or machine vision. This paper concerns about one of the categories in steganography on medium of text called text steganography that specifically focus on feature-based method. This paper reviews some of previous research effort in last decade to discover the performance of technique in the development the feature-based on text steganography method. Then, ths paper also concern to discover some related performance that influences the technique and several issues in the development the feature-based on text steganography method.